Soft-repair technique for solving inherent oversizing effect on multiple rooftop units in commercial buildings - Woradechjumroen, Denchai; Li, Haorong; Yu, Yuebin (Building and environment, 2016)
Rooftop packaged air-conditioning units (RTUs) have been intensively utilized in commercial buildings for providing space heating and cooling. They serve over 60% of the commercial building floor space in the U.S. Specifically, oversizing is an inherent issue practically caused by over design of mechanical engineers. With field test studies, oversizing can be up to 100% leading to high energy penalty. Although there are locally advanced control technologies utilized to improve the overall efficiency performance of RTUs, they are invasive approaches to interrupt normal operations and require experienced service teams for preventative maintenance causing high cost installation and service costs. The article proposes a novel and non-invasive methodology for permanently reducing the oversizing caused by non-optimal design or faulty design called “soft-repair”. The technique composes of coordination control and oversizing analysis to ultimately eliminate the fault impact without retrofitting original control. Control algorithms are systematically developed to mainly reduce oversizing effect utilizing simplified instantaneous building load for approximately quantify actual building load. With the control algorithm tested by a building simulation platform, the oversizing effect can be decreased at least 30% by comparing oversizing parameter signature of the original oversizing system with the improved results of soft-repair implementation because a suitable number and time operations of RTUs are automatically computed based on the actual building load and the soft-repair algorithm. With the decrease of the oversizing effect and energy penalty, the improve results lead to energy savings and extended life cycle of compressors, condenser fans and supply fans. •The article proposes a novel and non-invasive methodology for permanently reducing energy penalty caused by non-optimal design.•The technique uses coordination control and oversizing analysis to minimize the fault impact tested by a building simulation platform.•The technique leads to energy savings and extended life cycle of compressor, condenser fan and supply fan without original system interference.